Peningkatan Produktivitas UMKM Kue Kering dan Tik Tuk di Desa Cipanas Melalui Program Pendampingan Community Development - Soetijoso, Winnie Wiwa; Saputera, Miranda Indira; Anindhita, Shabira; Dwiputra, Mahardika; Andika, Rivo; Gerardo, Erick; Putra, Aditya Santosa; Paramita*, Kartika (Journal Pemberdayaan Masyarakat Indonesia, 2019)
The Community Development Program aims to help The Micro Small & Medium Enterprises (MSME) in developing their business. Through this activity, it is intended for builders to be able to increase sales and marketing widely. The method used is mentoring and monitoring of the direct practices applied by partners regarding the production process of cookies and tik-tuk. The success of this activity is in the form of a standard operating procedure (SOP). Partners also get additional equipment that supports the production process. Marketing partner products is made online to reach a broad target market. Product innovation starts from the presence of brands, logos, and packaging made to attract customers with new products introduced to the market.